Microscope-controlled glass bead blasting: a new technique - Peter Kotschy; Sascha Virnik; Doris Christ; et al (Clinical, Cosmetic and Investigational Dentistry, 2011)
Peter Kotschy1, Sascha Virnik2, Doris Christ3, Alexander Gaggl21Private Practice, Vienna, Austria; 2Department of Oral and Maxillofacial Surgery, Central Hospital, Klagenfurt, Austria; 3Klagenfurt, AustriaObjective: The aim of periodontal therapy is the healing of periodontal inflammation; the protection of the attachment and the alveolar bone; and the regeneration of the periodontal structures. In the therapy of periodontitis, supra- and subgingival scaling and root planing plays a main role. The procedure described combines perfect root cleaning without scaling and root planing and minimal invasive periodontal surgery without a scalpel.Material and methods: Glass beads of 90 µm were used with the kinetic preparation unit PrepStart® under a pressure of 0.5–5 bar. This technique was practised only under visual control using the OPMI® PRO Magis microscope. Seven examinations were carried out at baseline after 3, 6, 12, 18, 24, and 36 months.Results: Time shows a statistically significant influence on all of the considered target variables (P < 0.0001 for all). As the according estimate is negative, probing depth decreases over time. The major decrease seems to be during the first 6 months. Considering probing depth, plaque on the main effect root shows significant influence (again, P < 0.0001 for all). Observations with high probing depth at the beginning were faster than those with low probing depth. The same characteristic appears by attachment level. Patients with more loss of attachment show more gain.Conclusions: Using microscope-controlled glass bead blasting results in a perfectly clean root surface using visual control (magnification 20×). Microscope-controlled glass bead blasting is therefore a good alternative to periodontal surgery.Keywords: periodontal therapy, microscope, periodontitis